Low back pain and disability in military police: an epidemiological study - Edeildo Simplício Cardoso; Sabrina Gabrielle Gomes Fernandes; Luana Caroline de Assunção Cortez Corrêa; Glauko André de Figueirêdo Dantas; Saionara Maria Aires da Câmara (Editora Champagnat, 2018)
Abstract Introduction: The low back pain is a major public health problem in industrialized societies, commonly affecting the adult population. The occupation is considered as a risk factor, especially those functions that require physical effort, we have as example the job of the military police, who are exposed to several risk factors, both those who perform administrative activities, and those who perform the ostensive policing. Objective: The aim of this study was to evaluate the prevalence of low back pain among military police, as well the presence of disability and associated factors. Methods: This is an analytical cross-sectional study. Was evaluated the level of disability, pain before and after the work shift, flexibility, postural alterations and anthropometric measures. It was used the regression analysis, considering 95% CI and p < 0.05. Were interviewed 97 military police with mean age of 39.30 (± 5.33), all males. Results: The complaint of low back pain was significantly larger after the work shift, and 82.5% reported difficulties in daily life activities due to low back pain. Conclusion: There is a high prevalence of low back pain and impairment in daily life activities because of military police. The data presented reinforce the need to consider low back pain as a public health problem that affects the whole population, especially the military police.